The Reasons People Want to Quit Their Jobs in Baku at Public Sector Over the Last Decade - Guliyeva, Sabina (My University, 2026)
The present research seeks to identify the main causes of employee turnover in public sector of Baku, Azerbaijan during the last 10 years. Using semi-structured interviews of 17 respondents, the paper points the main factors that lead to job-leaving. Low pay is the most reported reason for leaving; however, the study indicates a nuanced relationship among financial, administrative, and psychosocial influences on turnover. The study identified key themes, including inadequate compensation and benefits, rigid and unattractive working conditions, deficient leadership and organizational culture, limited career development opportunities and individual alignment and career repositioning. That push-pull effect is echoed at a generational level, as younger workers desire flexibility, fast advancement and mission-driven work and as older employees value stability and predictability. While low pay is commonly cited as the number one reason for exit, the report insists that staff turnover is a multi-dimensional problem that requires systemic overhaul. This paper further recommends developing payment and grading policy, embracing flexible work programs, investing in leadership development, shifting to merit-based progression, and aligning culture with the changing expectations of workers. Although the qualitative design provides rich information, mixed-methods research is suggested for future research that increases generalizability. Dealing with these linked problems can enhance retention, job satisfaction, and the long-term health of public sector institutions.
Keywords: Employee retention -- Azerbaijan -- Baku.; Civil service -- Azerbaijan -- Baku -- Personnel management.; Compensation management -- Azerbaijan.; Baku (Azerbaijan) -- Officials and employees.; Azerbaijan -- Officials and employees.